Family Privacy As Protection: A Qualitative Pilot Study Of Mental Illness In Arab-American Muslim Women - Hassouneh, Dena (Research in the social scientific study of religion, 2009)
Arab-American Muslim women are a group whose cultural beliefs about mental illness are poorly understood. Moreover, the availability of literature specific to this population is limited. To begin to address the paucity of information available we conducted a qualitative pilot study. The overall aim was to preliminarily explore contexts and meanings about mental illness in Arab-American Muslim women. Interviews with eight women were completed. Data analysis occurred concurrently with data collection using an iterative process. The central theme identified in the narratives was family privacy as protection. The study’s primary conclusion is that an in-depth understanding of the meaning of family in Arab-American Muslim women’s lives is critical to our ability to effectively address their mental health needs.